1979
DOI: 10.1073/pnas.76.4.1682
|View full text |Cite
|
Sign up to set email alerts
|

Limited action of micrococcal nuclease on trout testis nuclei generates two mononucleosome subsets enriched in transcribed DNA sequences.

Abstract: Hybridization experiments show that DNA extracted from two distinct subsets of mononucleosomes (MN1 and MN2) generated by a limited action of micrococcal nuclease on trout testis nuclei is enriched t7-fold in sequences that are transcribed into cytoplasmic polyadenylated RNA in trout testis cells. Both subsets of mononucleosomes contain eight core histones, but MN1 also possesses one or two molecules of a small, basic, high-mobility-group (HMG) protein H6 [Levy W., B., Connor, W. & Dixon, G. H. (1979) J. BioL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Our findings have important implications relating to the function of the HMG proteins. These proteins are associated preferentially with transcriptionally competent chromatin (2)(3)(4)(5) and are thought to modify the basic structure of chromatin in such a way as to allow transcription to occur (9). Earlier estimates, however, suggested that the quantities of HMG proteins in the cell were not sufficient to saturate the highaffinity binding sites on each transcriptionally competent nucleosome (9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have important implications relating to the function of the HMG proteins. These proteins are associated preferentially with transcriptionally competent chromatin (2)(3)(4)(5) and are thought to modify the basic structure of chromatin in such a way as to allow transcription to occur (9). Earlier estimates, however, suggested that the quantities of HMG proteins in the cell were not sufficient to saturate the highaffinity binding sites on each transcriptionally competent nucleosome (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Considerable interest in the HMG proteins has been generated by reports that they are preferentially associated with transcriptionally competent portions of the genome (2)(3)(4)(5), and a great deal of effort is currently being expended to define the role which these proteins play in transcription. Not all investigators have found such a relationship .…”
mentioning
confidence: 99%
“…In addition to the histones, considerable attention has been focused on another group of chromosomal proteins, the high mobility group (HMG) proteins originally isolated from calf thymus nuclei . Although some of the HMG proteins appear clustered in the transcriptionally active regions of chromatin (Levy-Wilson et al, 1979;Weisbord et al, 1979), the precise function of these non-histone chromo-0006-2960/85/0424-1806S01.50/0 © 1985 American Chemical Society somal proteins still remains to be determined. Nevertheless, since the early studies on calf, proteins resembling HMGs have been isolated and characterized from a wide variety of eucaryotic cell types [for a review, see Mayes (1982)], including two lower eucaryotes: Tetrahymena (Hamana et al, 1979) and yeast (Petersen & Sheridan, 1978;Spiker et al, 1978;Weber & Isenberg, 1980).…”
mentioning
confidence: 99%
“…The elucidation of the structure of the chro-has been discovered that transcription of a spematin and the specific interactions between cific chromatin region is accompanied by a dis-DNA and chromatin proteins is a prerequisite ruption of some of the organizational features of for understanding the control ofgene expression. the chromatin, resulting in an increased DNase The concept that structural changes occurring sensitivity of actively transcribed genes (6, 16-within the chromatin complex are responsible 19,27,28,34,35).…”
mentioning
confidence: 99%